The nature of justice in the perspective of the philosophy of science - Warka, Made (Technium Social Sciences Journal, 2023)
In theory, sources of knowledge might also originate from the outcomes of reflection or contemplation rather than just from experimental or study results. A philosopher engages in reflection or contemplation when attempting to understand or identify the core of something having to do with legal principles. What is meant by justice is the most important philosophical topic when discussing the nature of justice. That is a question that pertains to the field of science philosophy. According to its core, the philosophy of science is a branch of general philosophy that provides responses to a number of inquiries regarding the nature of science. Science philosophy examines the philosophical underpinnings, presumptions, and implications of science, including the social and natural sciences. Philosophy of science studies the philosophical foundations, assumptions and implications of science, including the natural sciences and social sciences. Philosophy of science is closely related to epistemology and ontology.